Application of fuzzy AHP method based on eigenvalues for decision making in transportation problems - Dasril, Yosza; ., Muhammad Sam’an; Bujang, Nazarudin; Ramlan, Rohaizan (Penerbit UTHM, 2020)
There is extensive evidence that current environmental systems are at alarming level of degradations which can cause unfavourable impacts on human life and other interacting ecosystems. Consequently, firms were driven to review their current practices and identify any opportunity of introducing green initiatives in their operations to support the ability of current generations to meet their needs without compromising the ability of meeting needs of future generations. The strategic incorporation of environmental concerns in firm’s innovation efforts has been recognized to have great potential for supporting sustainable development (Xavier, 2015). Ecological innovation (eco-innovation) is one of the indispensable strategies for firms to overcome the increasing environmental challenges and contribute to achieve improved and sustainable environment. According to Tarnawska (2013), eco-innovations are basic sources of ecological growth and efficiency which resulted in technological improvements and greater sustainability. Thus, over the past two decades, firms were actively searching for the secret recipe on how to integrate the principles of eco-innovation into their long and short-term strategies.